2-Oxoamide inhibitors of phospholipase A2 activity and cellular arachidonate release based on dipeptides and pseudodipeptides - Barbayianni, E.; Stephens, D.; Grkovich, A.; Magrioti, V.; Hsu, Y. H.; Dolatzas, P.; Kalogiannidis, D.; Dennis, E. A.; Kokotos, G. (Bioorganic and Medicinal Chemistry, 2009)
A series of 2-oxoamides based on dipeptides and pseudodipeptides were synthesized and their activities towards two human intracellular phospholipases A2 (GIVA cPLA2 and GVIA iPLA2) and one human secretory phospholipase A2 (GV sPLA2) were evaluated. Derivatives containing a free carboxyl group are selective GIVA cPLA2 inhibitors. A derivative based on the ethyl ester of an ether pseudodipeptide is the first 2-oxoamide, which preferentially inhibits GVIA iPLA2. The effect of 2-oxoamides on the generation of arachidonic acid from RAW 264.7 macrophages was also studied and it was found that selective GIVA cPLA2 inhibitors preferentially inhibited cellular arachidonic acid release; one pseudodipeptide gave an IC50 value of 2 μM.
Keywords: 2-Oxoamides; Dipeptides; Inhibitors; Phospholipase A2; Pseudodipeptides